AVCL: Audio Video clustering for learning Conversation labeling using Neural Network and NLP - Chowdhury, Salman Mostafiz; Rohid, Ali Ahammed; Hussain, Rizwan; Mostafa, Chowdhury Sujana (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022